Adiponectin and Leptin are Secreted Through Distinct Trafficking Pathways in Adipocytes - Xie, Linglin (2008)
Adiponectin and leptin are two adipokines secreted by white adipose tissue that regulate insulin sensitivity. Previously we reported that adiponectin but not leptin release depends on GGA-coated vesicle formation, suggesting that leptin and adiponectin may follow different secretory routes. Here we have examined the intracellular trafficking pathways that lead to the secretion of these two hormones. While adiponectin and leptin displayed distinct localization in the steady-state, treatment of adipocytes with brefeldin A inhibited both adiponectin and leptin secretion to a similar level, indicating a common requirement for class III ADP-ribosylating factors and an intact Golgi apparatus. Adiponectin secretion was significantly reduced by endosomal inactivation in both 3T3L1 and rat isolated adipocytes, whereas this treatment had no effect on leptin secretion. Importantly, endosomal inactivation completely abolished the insulin stimulatory effect on adiponectin release in rat adipocytes. Confocal microscopy studies revealed colocalization of adiponectin with endogenous rab11 a marker for the recycling endosome, and with expressed rab5-GFP mutant (rab5Q75L) a marker for the early endosome compartment. Colocalization of adiponectin and rab5Q75L was increased in endosome inactivated cells. Consistent with these findings adiponectin secretion was reduced in cells expressing mutants of Rab11 and Rab5 proteins. In contrast, expression of an inactive (kinase dead) mutant of Protein Kinase D1 moderately but significantly inhibited leptin secretion without altering adiponectin secretion. Taken together, these results suggest that leptin and adiponectin secretion involve distinct intracellular compartments and that endosomal compartments are required for adiponectin but not for leptin secretion.